A companion to photography - Bull, Stephen, 1971- (Jphn Wiley & Sons, 2020)
"A Companion to Photography presents a contemporary approach to the subject, advancing the critical ideas that inform the study of photography in the 21st century. Features a collection of original, up-to-date essays relating to contemporary photography Introduces several new ideas that expand current photographic theory Combines essays by established and emerging writers, providing a dynamic and engaging discussion Essays are organized in thematic sections: photographic interpretation, markets, popular photography, documents, and fine art Seamlessly incorporates discussion of digital photography throughout"- Resumé vydavatel
Keywords: fotografování; fotografování -- filozofické aspekty; umělecká fotografie; photography; photography -- philosophical aspects; artistic photography; elektronické knihy; eseje; kolektivní monografie; electronic books; essays; collective monographs